A study of beamforming and beamshaping techniques for uniformly and non-uniformly spaced arrays - Lemes, Daniel Lima (2018)
The main goal of this work was to develop a MATLAB-based co de capable of finding the optimum values for amplitudes, phases and spacings of a non-uniformly spaced linear antenna array for a specified purpose. This tool allowed investigating the influence of the relative spacings between the elements of an antenna array in its radiation pattern. Two optimization methods were implemented: PSO (Particle swarm optimization), which is an evolutionary heuristic based on the social interaction and movement of swarms, and Taguchi’s method, which is based on orthogonal arrays to reduce the number of experiments needed to find the optimum value of a given variable. Different optimization goals were investigated, so that a comparison between these techniques has been done. The developed co de was applied to solve two practical problems. In the first one, a dual-band antenna array for base stations of mobile communication systems was modeled and its amplitudes, phases and spacings were optimized. By doing so, it was possible to mitigate the granting lobes that app eared in the pattern in the higher band, because the relative spacings between the elements could not be smaller than λ0. The pattern of this array was also shaped following a squared cosecant contour, in order to illuminate a pico-cell with uniform power. The results of the optimizations in both bands were validated using the commercial software Ansys HFSS and a study about the influence of the mutual coupling in the pattern was done. The second practical problem was to design an antenna array with beamshaping. By using the proposed code, it was possible to reduce the number of array elements from seven to four comparing to an uniformly spaced array. The optimization was split into two parts in order to mitigate the influence of the mutual coupling. A passive feeder for the optimized array was designed and a prototype was manufactured. The results were validated using HFSS and by measurements. The complete development of the array and of the feeder are detailed in this work. Finally, the design of a transmitter for adaptive beamshaping is described. The architecture nis capable to change the phase and power level of the signal, hence allowing to deliver the weights optimized by the proposed code to the antenna array. A modular concept was chosen in order to increase the flexibility of the transmitter. The device translates the input frequency from 500 MHz to 7 GHz, in order to deliver the weights to the antenna array. Eight transmitters were assembled and they were coupled to the antenna array in order to test their functionality. The patterns were measured in an anechoic chamber. All measured results of the transmitter are presented.